Progressive collapse of reinforced concrete flat slab structures - Russell, Justin (2015)
In 1968 a relatively small gas exposition on the 18th floor of the Ronan Point tower building resulted in the partial collapse of the structure. This event highlighted that progress collapse may occur to structures under an accidental loading event. Other events, including the bombing of the Murrah federal building in 1993 in Oklahoma, have resulted in the common design requirement that a structure be capable of surviving the removal of a load bearing element. This approach, often referred to as the sudden column loss scenario, effectively ignores the cause of the damage and focuses on the structure’s response afterwards. The refinement of the analysis varies, with options to include the nonlinear and dynamic behaviours associated with extreme events, or to use simplified linear and static models with factors included to account for the full behaviour.